Income transfers, welfare and family decisions - Joaquín Andaluz; Miriam Marcén; José Alberto Molina (Institute for the Study of Labor (IZA), 2007)
This paper studies the effects of different income transfers on individual welfare, in both marriage and divorce situations, and on family decisions. We assume three generations within the family. We develop a sequential game that, in a first stage, determines the optimum level of the transfer within a relationship of one-sided altruism. In the second stage, the level of welfare is deduced by way of a Nash bargaining solution. We show that inter-generational transfers may produce losses derived from the marriage. We have also found that the donor of an intergenerational transfer can behave in a compensatory way in an altruism model.
urn:nbn:de:101:1-20080401261
Keywords: 330; Privater Transfer; Familienökonomik; Ehe; Wohlfahrtseffekt; Extensives Spiel; Nash-Gleichgewicht; Altruismus; Theorie